Relative Adrenal Insufficiency in Pediatric Septic Shock - Vila-Pérez, David; Jordan-García, Iolanda (Journal of Pediatric Intensive Care, 2015)
Sepsis and septic shock represent important causes of morbidity and mortality in children, and adrenal dysfunction may play a role in the cardiovascular and immunological response. According to existing reports, the incidence of adrenal dysfunction in critically ill children varies significantly between 4 and 52% of patients. This article reviews the concept of adrenal insufficiency and the role it may play in a pediatric septic shock. Also discussed are the diagnosis, prognosis, and treatment of adrenal insufficiency in septic shock in adults and children. Finally, the latest recommendations about steroid use in pediatric septic shock are summarized.
Keywords: sepsis; septic shock; pediatric septic shock; adrenal insufficiency; relative adrenal insufficiency